Supraspinatus-to-Glenoid Contact Occurs During Standardized Overhead Reaching Motion. Issue 10 (5th October 2021) - Saini, Gaura; Lawrence, Rebekah L.; Staker, Justin L.; Braman, Jonathan P.; Ludewig, Paula M.
Background: Rotator cuff tears may result from repeated mechanical deformation of the cuff tendons, and internal impingement of the supraspinatus tendon against the glenoid is one such proposed mechanism of deformation. Purpose: To (1) describe the changing proximity of the supraspinatus tendon to the glenoid during a simulated overhead reaching task and (2) determine the relationship between scapular morphology and this proximity. Additionally, the patterns of supraspinatus-to-glenoid proximity were compared with previously described patterns of supraspinatus-to-coracoacromial arch proximity. Study Design: Descriptive laboratory study. Methods: Shoulder models were created from magnetic resonance images of 20 participants. Standardized kinematics were imposed on the models to simulate functional reaching, and the minimum distances between the supraspinatus tendon and the glenoid and the supraspinatus footprint and the glenoid were calculated every 5° between 0° and 150° of humerothoracic elevation. The angle at which contact between the supraspinatus and the glenoid occurred was documented. Additionally, the relationship between glenoid morphology (version and inclination) and the contact angle was evaluated. Descriptive statistics were calculated for the minimum distances, and glenoid morphology was assessed using Pearson correlation coefficients and simple linear regressions. Results: The minimum distances between the tendon and the glenoid and between the footprint and the glenoid decreased as elevation increased. Contact between the tendon and the glenoid occurred in all participant models at a mean elevation of 123° ± 10°. Contact between the footprint and the glenoid occurred in 13 of 20 models at a mean of 139° ± 10°. Less glenoid retroversion was associated with lower tendon-to-glenoid contact angles ( r = –0.76; R 2 = 0.58; P < .01). Conclusion: This study found that the supraspinatus tendon progressively approximated the glenoid during simulated overhead reaching. Additionally, all participant models eventually made contact with the glenoid by 150° of humerothoracic elevation, although anatomic factors influenced the precise angle at which contact occurred. Clinical Relevance: Contact between the supraspinatus and the glenoid may occur frequently within the range of elevation required for overhead activities. Therefore, internal impingement may be a prevalent mechanism for rotator cuff deformation that could contribute to cuff pathology.